2017
DOI: 10.1002/for.2461
|View full text |Cite
|
Sign up to set email alerts
|

The informational content of unconventional monetary policy on precious metal markets

Abstract: This paper investigates the informational content of unconventional monetary policies and its effect on commodity markets, adopting a nonlinear approach for modeling volatility. The main question addressed is how the Bank of England, Bank of Japan, and European Central Bank's (ECB's) announcements concerning monetary easing affect two major commodities: gold and silver. Our empirical evidence based on daily and high-frequency data suggests that relevant information causes ambiguous valuation adjustments as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…The influence of the ECB's announcements is much weaker. In contrast to Papadamou and Sogiakas (2018), the authors do not find any reactions of gold price to QE news announcements from either the Bank of England or the Bank of Japan.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The influence of the ECB's announcements is much weaker. In contrast to Papadamou and Sogiakas (2018), the authors do not find any reactions of gold price to QE news announcements from either the Bank of England or the Bank of Japan.…”
Section: Introductioncontrasting
confidence: 99%
“…To now, only few papers have been focused on the effects of ECB's unconventional monetary announcements on commodity markets. For instance, Papadamou and Sogiakas (2018) show that the response of precious metal prices to such monetary news appears not significant or even negative. Unlike to the ECB announcements, those from the Japanese Central Bank improve the precious metal markets in terms of higher returns and stabilization impact.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that this instrument has contributed to a decline on covered bond spreads, namely, during the first week after the programme announcement. Finally, Papadamou and Sogiakas (2018) find that the ECB's unconventional monetary policies have an insignificant or even a negative impact on precious metal prices. Angelini, Nobili, and Picillo (2011) find that such measures reduced the long-term interbank spread only after the failure of Lehman Brothers.…”
Section: Introductionmentioning
confidence: 91%
“…Brunetti, di Filippo, and Harris (2011) find that the non-standard monetary programs lead to higher uncertainty in money markets. Finally, Papadamou and Sogiakas (2018) find that the ECB's unconventional monetary policies have an insignificant or even a negative impact on precious metal prices.…”
Section: Introductionmentioning
confidence: 91%
“…The literature on the impacts of unconventional monetary practices has been mainly focused on the values of assets, such as stock prices (Bowman et al 2015;Fratzscher et al 2017), exchange rates (Kenourgios et al 2015a(Kenourgios et al , 2015bLin et al 2017;MacDonald 2017), bond yields (D'Amico and King 2013; Bauer and Neely 2014;Papadamou et al 2018b), banks (Von Borstel et al 2016), and commodities (Papadamou and Sogiakas 2018). Moreover, a meta-analysis was recently conducted on the empirical findings on the macroeconomic effects of unconventional policies (Papadamou et al 2018a).…”
Section: Introductionmentioning
confidence: 99%